Solution of Homogeneous Fredholm Integral Equations of the Second Kind - Jebran, Samaruddin (Journal of Natural Sciences – Kabul University, 2021)
Significant advancements have been made in the theory of integral equations. The division of initial value problems into Volterra Integral Equations and boundary value problems into Fredholm Integral Equations is an essential framework. Simplifying these equations requires focusing on the kernel and considering various cases of it. In this study, only the Homogeneous Fredholm Integral Equations of the second kind are discussed. The article begins with an exploration of key concepts such as eigenvalues, eigenfunctions, and the related theorems, providing a comprehensive explanation of their roles.